A descriptive model of the offence process for animal abusers: evidence from a community sample - Ford, Jade (Psychology, crime & law, 2021)
Animal abuse perpetrated by adults is prevalent, yet largely undetected and understudied. As a result, clinicians have a limited evidence base to draw from when working with animal abusers. The primary aim of this study was to develop the first descriptive model of the offence process for animal abusers using a community sample. Participants were recruited via Prolific Academic - an online crowdsourcing platform that enables cost-effective recruitment of diverse participant pools from the UK. We identified 198 animal abusers in our survey and administered a series of open-ended qualitative items asking participants to describe the circumstances leading up, during, and after the offence. Employing Strauss and Corbin’s (1990) [Strauss, A., & Corbin, J. (1990). Basics of qualitative research: Grounded theory procedures and techniques. Newbury Park, CA: Sage.] grounded theory analysis, we coded the qualitative responses and developed the offence process model. The model detailed the cognitive, behavioral, affective, and contextual factors across the timespan of the animal abuse behavior (i.e. background, pre-offence, offence, and post-offence). This descriptive model of the offence process for animal abusers highlights key targets throughout the timespan that can inform prevention and intervention strategies moving forward.